Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE), 2013 2013
DOI: 10.7873/date.2013.080
|View full text |Cite
|
Sign up to set email alerts
|

SMART: A Single-Cycle Reconfigurable NoC for SoC Applications

Abstract: Abstract-As technology scales, SoCs are increasing in core counts, leading to the need for scalable NoCs to interconnect the multiple cores on the chip. Given aggressive SoC design targets, NoCs have to deliver low latency, high bandwidth, at low power and area overheads. In this paper, we propose Single-cycle Multihop Asynchronous Repeated Traversal (SMART) NoC, a NoC that reconfigures and tailors a generic mesh topology for SoC applications at runtime. The heart of our SMART NoC is a novel low-swing clockles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…This limits latency and throughput savings possible in the context of a multi-hop NoC that requires a more global view of control. For example, using on-demand routing [4], packets can continue to spend multiple cycles in local and global arbitration every time the packet stops short of its destination due to contention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This limits latency and throughput savings possible in the context of a multi-hop NoC that requires a more global view of control. For example, using on-demand routing [4], packets can continue to spend multiple cycles in local and global arbitration every time the packet stops short of its destination due to contention.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, each router in the NoC independently arbitrates and routes locally for traversal to adjacent nodes. Recent research proposes to utilize a clockless repeater link to perform more global control and multi-hop traversal [4] to provide dramatic improvements in message latency and network power consumption. However, this previous work still utilizes basic assumptions of on-demand message routing suitable for distributed control even though messages require coalescing of multiple nodes' arbitration and routing.…”
Section: Introductionmentioning
confidence: 99%
“…A test chip at 45nm recently demonstrated that clockless repeated links can go up to 13mm with 1.0V full-swing (16mm with 300mV low-swing) within 1ns [11]. Post-layout simulations of the synthesized SMART control and data paths in 45nm indicate that SSR traversal followed by arbitration limits the speed to 9-11mm/ns [29].…”
Section: Background: Smart Nocmentioning
confidence: 99%
“…Link improvement: Low-swing signalling [20] and an asynchronous link [21,22] have been adopted in NoCs to allow multiple-hop traversal in one cycle. Low-swing signalling has poor bandwidth density, and the asynchronous link can have signal skew issues due to interference [23].…”
Section: Noc Router Architecture and Algorithmsmentioning
confidence: 99%